Constitution USA [videorecording (DVD)] : with Peter Sagal - Ives, Stephen; Sagal, Peter; Sagal, Peter (PBS Distribution, 2013)
Breathing new life into the traditional civics lesson, Peter Sagal travels across the country on a Harley Davidson to find out where the U.S. Constitution lives, how it works and how it doesn't, how it unites us as a nation and how it has nearly torn us apart.